Charge density mapping demonstrates superiority in catheter ablation of post-surgical atrial tachycardias - Gagyi, Rita B.; Minciuna, Ioan A.; Bories, Wim; Szili-Torok, Tamas (Frontiers in Cardiovascular Medicine, 2024)
Introduction Atrial tachycardia (AT) frequently occurs after cardiac surgery or surgical ablation procedures. The novel charge density-based mapping system (CDM) provides global chamber mapping and can detect crucial pathways of conduction; therefore, it has potential added value in catheter ablation (CA) of post-surgical ATs. We aimed to test the hypothesis that CDM-guided CA procedures are safe, feasible, and may improve outcome compared to conventional sequential 3D mapping (CARTO)-based CA. Methods and results Consecutive patients undergoing CA for post-surgical AT guided by CDM or CARTO were enrolled. Procedural safety and efficiency were analyzed. Acute success, one-year outcome was assessed. A total of 35 patients (mean age 60.8 ± 10.6 years, 42.9% female) underwent CA of AT using CDM (n = 20) and CARTO (n = 15). A total of 61 ATs were mapped (35 in CDM and 26 in CARTO group). Four patients had focal ATs, 22 macro re-entrant, and 8 patients had ATs with both mechanisms. No differences were found in procedural complication (CDM 3 vs. CARTO 1 patient, p = 0.61). There were no differences in procedure duration (185.9 vs. 147.9 min, p = 0.09), fluoroscopy dose (165.0 vs. 155.0 mGy, p = 0.31), RF application number (28.0 vs. 18.0, p = 0.17) or duration (1,251.5 vs. 1,060.0 s, p = 0.54). Acute success was 95.0% in CDM and 73.3% in CARTO group (p = 0.14). Cumulative AT recurrence rates were lower in CDM group compared to CARTO group (10.0% vs. 46.7%, p = 0.02). Conclusions The CDM system is feasible. Our data suggest that patients treated with CDM-guided CA developed fewer AT recurrences as compared to CARTO-guided procedures.